Status of Ocular Complications in Type 2 Diabetes and Relationship Between Other Comorbidities (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Introduction : Diabetes Mellitus is a multifactorial disease, associated with a number of micro vascular (Retinopathy, Neuropathy and Nephropathy) and macro vascular (Ischemic Heart Disease, Cerebrovascular Disease and Peripheral Vascular Diseases) complications. Duration of diabetes, current smoking and presence of co morbidities such as HTN, IHD all are significantly associated with the ocular complications in this study.Objective: The purpose of the study is to see the glycaemic status and co morbidities influencing the ocular complications.Methods: The patients for the study were randomly recruited from the Eye outpatient clinics in Chattagram Maa Shishu-O-General Hospital, Chittagong, Bangladesh, from July 2014 to October 2014. Risk factors of DR like age, sex, duration of diabetes and hypertension, IHD, smoking status were evaluated.Results: The study showed that 53 are male and 47 are female. Maximum age is 85 and minimum age is studied at 28. Cataract was the predominant complications presented our study. 22% patient had unilateral and 20% had bilateral cataract. 29% had retinopathy. Mean FPG , PPG & HBA1c levels in unilateral cataract were 7.0 mmol/L, 8.9 mmol/L and 7.03 mmol/L in comparative to retinopathy group was 8.4 mmol/L, 10.6 mmol/L and 8.6 mmol/L respectively. Major complications are retinopathy are found in 26% hypertensive and 24% IHD patients, prevalence of Diabetic retinopathy is 6.9% after 5 years onset of DM and 73.9% after 15 years of diabetes.Conclusion : Prevalence of Diabetic ocular complications is high in our country, Ocular complications increases proportionately to duration and presence of co morbidities. Tight control of DM and periodic eye examination can prevent complications.Chatt  Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 35-39